2013
DOI: 10.1002/andp.201300110
|View full text |Cite
|
Sign up to set email alerts
|

Detection of topological matter with quantum gases

Abstract: Creating and measuring topological matter -with non-local order deeply embedded in the global structure of its quantum mechanical eigenstates -presents unique experimental challenges. Since this order has no signature in local correlation functions, it might seem experimentally inaccessible in any macroscopic system; however, as the precisely quantized Hall plateaux in integer and fractional quantum Hall systems show, topology can have macroscopic signatures at the system's edges. Ultracold atoms provide new e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…A similar π flux also plays a crucial role in the nuclear dynamics of molecules featuring conical intersections of energy surfaces [2]. Our direct detection of the paradigmatic π flux demonstrates the capability to reveal even singular Berry flux fea- tures that are not observable by alternative techniques based on transport measurements [7,8,[17][18][19] and thereby paves the way to full topological characterization of optical lattice systems [18][19][20][21][22][23][24][25]. The effect of Berry curvature in our interferometer is analogous to the Aharonov-Bohm effect, where an electron wavepacket is split into two parts that encircle a given area arXiv:1407.5635v1 [cond-mat.quant-gas] 21 Jul 2014 The duration of the interferometer sequence is 2τ = 1.6 ms for all measurements.…”
mentioning
confidence: 87%
“…A similar π flux also plays a crucial role in the nuclear dynamics of molecules featuring conical intersections of energy surfaces [2]. Our direct detection of the paradigmatic π flux demonstrates the capability to reveal even singular Berry flux fea- tures that are not observable by alternative techniques based on transport measurements [7,8,[17][18][19] and thereby paves the way to full topological characterization of optical lattice systems [18][19][20][21][22][23][24][25]. The effect of Berry curvature in our interferometer is analogous to the Aharonov-Bohm effect, where an electron wavepacket is split into two parts that encircle a given area arXiv:1407.5635v1 [cond-mat.quant-gas] 21 Jul 2014 The duration of the interferometer sequence is 2τ = 1.6 ms for all measurements.…”
mentioning
confidence: 87%
“…By comparing to what would have happened in the symmetric gauge, we showed that the gauge choice can make a significant difference in the experimental outcome. In the future, techniques that match a system's geometry to the artificial field's natural gauge might be used to selectively excite edge modes in cold-atom quantum-Hall-like systems [18][19][20].…”
mentioning
confidence: 99%
“…In condensed matter physics, the topological charge pumping is not easily observed because of the challenging requirement for flexible Hamiltonian engineering. Ultracold atom systems, with the highly controllable properties, provide a perfect platform to observe these topological phenomena [6,7]. The charge pumping has already been observed experimentally in ultracold atom systems by driving a superlattice adiabatically [8,9].…”
mentioning
confidence: 95%